Pengaruh Model Flipped Classroom Berbantuan Video Interaktif YouTube terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas XI: The Effect of the Flipped Classroom Model Assisted by Interactive YouTube Videos on the Explanatory Text Writing Skills of Grade XI Students - Haekal Fardeni; Maplindo Maplindo; Intan Maulina (ITScience (Information Technology and Science), 2026)
This study was motivated by students' low proficiency in writing explanatory texts, particularly regarding the logical development of ideas, the coherent structuring of cause-and-effect relationships, and the accurate application of linguistic rules. The study aimed to determine the effect of using the Flipped Classroom model—supported by interactive YouTube videos—on the explanatory text writing skills of Grade XI students at MAS Al-Washliyah 49 Pasar Lembu. This research employed a quasi-experimental approach using quantitative methods and a posttest-only control group design. The study population comprised all Grade XI students at MAS Al-Washliyah 49 Pasar Lembu. The sample consisted of two classes—Class XI IPA 1 (experimental group) and Class XI IPA 2 (control group)—totaling 60 students. The Flipped Classroom model supported by interactive YouTube videos was implemented in the experimental class, while conventional instruction was used in the control class. Following the instructional period, the results showed an average score of 78.00 (categorized as